Uma proposta de abordagem dos números complexos com o uso do GeoGebra - Germano, José Gleisson da Costa (2016)
This work deals with a proposal that involves GeoGebra and complex numbers, so that it can be used in the classroom by Mathematics teachers of the Secondary School with appropriate due adaptations. Teaching situations were constructed and proposed, with the aim of proposing a didactic sequence, based on Guy Brousseau's Theory of Educational Situations (TSD); as well as methodological procedures were used in the scope of Didactic Engineering of Michele Artigue. In this investigation, the geometric interpretation takes place fundamentally, so that the use of GeoGebra can foment the visualization and instigate a possible learning. Thus, instead of just using conventional chalk (or brush) and blackboard in class, this paper proposes the use of this dynamic mathematical software in the course of Mathematics classes, highlighting the following items: geometric representation Of the set C, operations in C and movements in the plane (translation, homotetia and rotation). The research was salutary, considering that preliminary studies showed that the elaborate didactic sequence, supported by the use of GeoGebra, can corroborate the good teaching and learning of complex numbers. It is hoped that this work can be continued in order to allow a deeper understanding of the theme